2011
DOI: 10.1111/j.1538-7836.2011.04462.x
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus sanguinis‐induced cytokine release from platelets

Abstract: Summary. Background: There is increasing evidence that both chronic and acute infections play a role in the development and progression of atherothrombotic disorders. One potential mechanism is the direct activation of platelets by bacteria. A wide range of bacterial species activate platelets through heterogeneous mechanisms. The oral micro-organism S. sanguinis stimulates platelet aggregation in vitro in a strain-dependent manner, although there are no reports of associated cytokine production. Objective: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 88 publications
3
20
0
Order By: Relevance
“…CD62P is only released in the presence of one strain of S. sanguinis (82). Another study had also shown that platelets were capable of releasing soluble CD40L (sCD40L) and RANTES after stimulation with IgG-bead complexes, with the absence of aggregation and a very weak expression of CD62P (72).…”
Section: Effects Of Bacteria On Platelet Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD62P is only released in the presence of one strain of S. sanguinis (82). Another study had also shown that platelets were capable of releasing soluble CD40L (sCD40L) and RANTES after stimulation with IgG-bead complexes, with the absence of aggregation and a very weak expression of CD62P (72).…”
Section: Effects Of Bacteria On Platelet Functionmentioning
confidence: 99%
“…The mechanism of inhibition used is unknown but could be linked to the activation of type 3 nitric oxide synthase (NOS) after involvement of the β 2 adrenoreceptors; the resultant generation of nitric oxide (NO) and cGMP has already been described in platelet activation inhibition (82). This clearly demonstrates that platelet aggregation and exocytosis of immunomodulating molecules are two independent functions.…”
Section: Effects Of Bacteria On Platelet Functionmentioning
confidence: 99%
“…For S. sanguinis 2017-78 cytokine secretion was independent of thromboxane production and aggregation. Interestingly this secretion response was inhibited by low doses of epinephrine while aggregation and protein phosphorylation cascades mentioned previously were enhanced [99]. The inhibition of platelet activation by epinephrine has not been noted in response to any other platelet agonists and adds another layer of complexity to bacterial induced platelet activation.…”
Section: Streptococcal-platelet Interactions -Immunological Responsementioning
confidence: 82%
“…They examined platelet secretion of soluble inflammatory mediators (Platelet factor 4, RANTES, sCD40L, platelet derived growth factor) in response to a number of S. sanguinis and S. gordonii strains and paired these with their platelet aggregation responses. All strains triggered secretion of cytokines irrespective of the platelet aggregation response but only 1 strain (S. sanguinis 2017-78) triggered release of sCD62p [99]. For S. sanguinis 2017-78 cytokine secretion was independent of thromboxane production and aggregation.…”
Section: Streptococcal-platelet Interactions -Immunological Responsementioning
confidence: 84%
See 1 more Smart Citation